Pengaruh PENGARUH EDUKASI GIZI MENGGUNAKAN MEDIA SOSIAL INSTAGRAM TERHADAP PERUBAHAN PERILAKU GIZI SEIMBANG DAN AKTIVITAS FISIK REMAJA OVERWEIGHT DI MAN 1 ACEH BARAT TAHUN 2021 - Ranita Suri Dewi (Jurnal Komunitas Kesehatan Masyarakat, 2022)
The prevalence of overweight in adolescents aged 10-19 years globally is 17,3%. One of the causes overweight is due to lack of behavior as well as physical activity. Nutrition education can change a person's behavior. This study aims to see the effect of nutrition education using Instagram social media on balanced nutritional behavior and physical activity of overweight adolescents in MAN 1 Aceh Barat year 2021. The type of this research is quasi-experiment pre-post test with-control-group design. The media used is Instagram. The research was conducted in MAN 1 Aceh Barat from October 2020-June 2021. The sample consisted of 52 overweight students using Purposive Sampling. Before the nutrition education the adolescent had knowledge score of 5.73, attitude score of 24.73, action score of 6.50, physical activity score of 7.76, after nutrition education knowledge score of 8.88, attitude score of 33.69, action score of 6.65, physical activity score of 8.03. It showed there was a significant difference in knowledge (p-value 0.001) and attitude (p-value 0.001), there was no difference in action (p-value 0.476) and physical activity (p-value 0.056) on intervention group using Instagram. It is hoped the school can facilitate students to disseminate information of balanced nutrition using social media instagram.